PENGEMBANGAN DAN VALIDASI METODE PENETAPAN KADAR TABLET SIPROFLOKSASIN HIDROKLORIDA MONOHIDRAT MENGGUNAKAN FTIR - Laila Qodariah, Rismawati
Analytical method has to be developed continuously in order to obtain the finest and latest result of analysis. Spectrometer FTIR (Fourier-Transform Infrared Spectrometer) is an instrument that can be generally used for qualitative analysis, while the use of FTIR in quantitative analysis is still rare. Ciprofloxacin hydrochloride monohydrate (SHM) has OH hydrate stretching (3700-3500 cm -1 ) which can be observed clearly, therefore this hydrate spectrum can be chosen as basis for quantitative dosage calculation. The aim of this study is to develop and validate method in determining tablet of antibiotic SHM using FTIR. SHM standard in various levels were dispersed in KBr and measured their FTIR spectrums. FTIR spetrums were derivated to obtain derivative area (AUC). Determining content was obtained by transforming derivative area (AUC) of sample into calibration curve, plotted between concentration of SHM standard and derivative area (AUC). Developing method was then validated and tried to determine 4 products tablet of SHM which label claimed 500 mg. The result of this determination was then compared with antibiotic potency test microbiologically. Based on the comparison of the derivative spectrum. SHM standard and SHM tablet dosage forms were identic. Analytical method development obtained good linearity at concentration range 0.25-1.50% w/w SHM to KBr; with the calibration curve of y = 59.45x+21.08; and correlation coefficient of r = 0.9994 and Vxo = 2.0% . The limit detection (LOD) was 0.05% w/w, while limit quantitation (LOQ) was 0.18% w/w. The recovery of SHM was 99.03-100.71%. The % RSD for intra day precision was 1.15%; 1.31%; 1.41%,while % RSD for interday precision was 1.42%. Based on the result obtained, this developing method has fulfilled validation parameter and tried to be used for determining antibiotic SHM in tablet dosage forms. The result was compared with antibiotic potency test microbiologically using diffused agar method. It was obtained linearity at range 27.59-56.34 ?g/mL, y = 16.79 x –8.21 and correlation coefficient of r 2 = 0.98. All products met the specified requirements Indonesian Pharmacope V, based on FTIR and microbiology method. It was concluded that determining antibiotic SHM in tablet dosage forms using FTIR was validated and can be applied as an alternative method in determining antibiotic SHM in tablet with the trustworthly result.